C-shaped canal, an endodontic challenge - Vikram, Mannu (Health Renaissance, 2013)
Recognition of unusual variations in the canal configuration is critical because it has been established that the root with a single tapering canal and apical foramen is the exception rather than the rule. C-shaped canals are anatomic features that present the clinician with both diagnostic and operational challenges. The early recognition of these configurations facilitates cleaning, shaping, and obturation of the root canal system. .C. configuration, which is an important anatomic variation, presents a thin fin connecting the root canals.The C-shaped root canal system is an anatomical variant of the root canal structure in which a continuous slit or web connects individual root canals. These C-shaped canals present a challenge to the clinician, both at the diagnostic and treatment level. Health Renaissance, January-April 2013; Vol. 11 No.1; 89-91 DOI: http://dx.doi.org/10.3126/hren.v11i1.7610